2023
DOI: 10.1021/acsnano.3c03118
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared-Responsive Photocatalytic CO2 Conversion via In Situ Generated Co3O4/Cu2O

Abstract: Photocatalytic CO2 conversion to fuels is a promising strategy for achieving global carbon neutrality. However, infrared light, which accounts for ∼50% of the full sunlight spectrum, has not yet been effectively utilized via photocatalysis. Here, we present an approach to directly power photocatalytic CO2 reduction using near-infrared light. This near-infrared light-responsive process occurs on an in situ generated Co3O4/Cu2O photocatalyst with a nanobranch structure. Photoassisted Kelvin probe force microscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(21 citation statements)
references
References 69 publications
0
15
0
Order By: Relevance
“…The E fb of Co 3 O 4 was 2.06 V, which corresponded to a VB potential of 2.26 eV vs NHE and a CB potential of 0.22 eV vs NHE. false( α italichv false) 1 / n = A ( hv E normalg ) E g = E VB E CB Based on the above analysis, the energy band positions of n-type semiconductor Ni/Mn-MOF-74, n-type semiconductor CdS, and p-type semiconductor Co 3 O 4 before and after contact are shown in Figure g,h. The Fermi level of n-type semiconductor Ni/Mn-MOF-74 and CdS was closer to its CB, and the Fermi level of p-type semiconductor Co 3 O 4 was closer to VB. , When a p–n heterojunction was created, the p- and n-type semiconductors came into direct contact. This caused the band structure of the semiconductor to bend, resulting in the alignment of the Fermi levels of the p-type and n-type semiconductors.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…The E fb of Co 3 O 4 was 2.06 V, which corresponded to a VB potential of 2.26 eV vs NHE and a CB potential of 0.22 eV vs NHE. false( α italichv false) 1 / n = A ( hv E normalg ) E g = E VB E CB Based on the above analysis, the energy band positions of n-type semiconductor Ni/Mn-MOF-74, n-type semiconductor CdS, and p-type semiconductor Co 3 O 4 before and after contact are shown in Figure g,h. The Fermi level of n-type semiconductor Ni/Mn-MOF-74 and CdS was closer to its CB, and the Fermi level of p-type semiconductor Co 3 O 4 was closer to VB. , When a p–n heterojunction was created, the p- and n-type semiconductors came into direct contact. This caused the band structure of the semiconductor to bend, resulting in the alignment of the Fermi levels of the p-type and n-type semiconductors.…”
Section: Resultsmentioning
confidence: 92%
“…In order to differentiate between direct photooxidation with holes and indirect photooxidation with • O 2 – and OH • radicals, a series of experiments were conducted. These experiments involved the use of p-benzoquinone (PBQ) to quench • O 2 – radicals, citric acid (CA) to quench holes, and tert -butyl alcohol (TBA) to quench OH • radicals. , As depicted in Figure d, the addition of a quencher for • O 2 – radicals ( p -benzoquinone) led to a noticeable change in the degradation rate of TC. This indicated that the photoinduced electrons remained in the CB of Ni/Mn-MOF-74 and did not transfer to the CB of CdS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An efficient photothermal catalytic CO 2 reduction system should possess key features such as wide-spectrum absorption, effective photo-to-heat conversion, strong light-induced charge separation, multiple catalytic active sites, and a low energy barrier for CO 2 activation and conversion. Coupling a photothermal component with a photochemical active unit to construct heterojunctions holds great promise for maximizing photothermal CO 2 reduction activity. , This approach integrates the driving forces of both photocatalytic and thermal active components for breaking the CO bond in CO 2 . Additionally, it promotes charge carrier separation via a built-in heterojunction and affords multiple catalytic active sites accompanied by synergetic charge redistribution.…”
Section: Introductionmentioning
confidence: 99%
“…Coupling a photothermal component with a photochemical active unit to construct heterojunctions holds great promise for maximizing photothermal CO 2 reduction activity. 20,21 This approach integrates the driving forces of both photocatalytic and thermal active components for breaking the C�O bond in CO 2 . Additionally, it promotes charge carrier separation via a built-in heterojunction and affords multiple catalytic active sites accompanied by synergetic charge redistribution.…”
Section: ■ Introductionmentioning
confidence: 99%